2021
DOI: 10.1186/s12302-021-00487-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating ecological risks and tracking potential factors influencing heavy metals in sediments in an urban river

Abstract: Background Heavy metal pollution of aquatic systems is a global issue that has received considerable attention. Canonical correlation analysis (CCA), principal component analysis (PCA), and potential ecological risk index (PERI) have been applied to heavy metal data to trace potential factors, identify regional differences, and evaluate ecological risks. Sediment cores of 200 cm in depth were taken using a drilling platform at 10 sampling sites along the Xihe River, an urban river located in we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 46 publications
1
9
1
Order By: Relevance
“…A higher mean Pb level (169.8 mg/kg) was reported in Deepor Beel, a Ramsar site and of the largest freshwater lakes of the Brahmaputra Valley, located in Guwahati city, Assam, India [ 36 ]. The maximum Pb content in the current study is lower than that reported in Kinshasa City, Congo urban rivers and other urban rivers across the world [ 7 ], Langat River, Malaysia [ 5 ], river Hindon, India [ 8 ], and urban river sediments in China [ 10 , 13 , 37 ] but was higher than those reported in river Couvary, India [ 38 ], river Ganga, India [ 39 ], urban river sediments in China [ 1 , 33 , 40 ].…”
Section: Resultscontrasting
confidence: 78%
See 3 more Smart Citations
“…A higher mean Pb level (169.8 mg/kg) was reported in Deepor Beel, a Ramsar site and of the largest freshwater lakes of the Brahmaputra Valley, located in Guwahati city, Assam, India [ 36 ]. The maximum Pb content in the current study is lower than that reported in Kinshasa City, Congo urban rivers and other urban rivers across the world [ 7 ], Langat River, Malaysia [ 5 ], river Hindon, India [ 8 ], and urban river sediments in China [ 10 , 13 , 37 ] but was higher than those reported in river Couvary, India [ 38 ], river Ganga, India [ 39 ], urban river sediments in China [ 1 , 33 , 40 ].…”
Section: Resultscontrasting
confidence: 78%
“…Similarly, the maximum concentration of Zn reported in the river Bharalu was lower than those reported in urban rivers of Kinshasa City, Congo [ 7 ], river Couvary, India [ 38 ], Turag River, Bangladesh [ 41 ], urban river sediments, China [ 1 , 10 , 33 , 40 , 42 ] but was higher than those reported in Langat River, Malaysia [ 5 ] and river Ganga, India [ 39 ]. The maximum Ni level was lower than those reported in river Hindon, India [ 8 ], and urban river sediments in China [ 7 , 37 , 42 ].…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Pollution of water systems with heavy metals resulting from industrial activities and social-economic development has evolved a global environmental problem that has obtained wide attention due to the high toxicity of these metals and their non-dissolution and stability [1][2]. Interest in sediment pollution has increased because it represents an important evidence of environmental change caused by human activities [3].…”
Section: Introductionmentioning
confidence: 99%